Effect of viscoelastic properties of cellulose nanocrystal/collagen hydrogels on chondrocyte behaviors - Liu, Donglei; Zhang, Hao; Dong, Xufeng; Sang, Lin; Qi, Min (Frontiers in Bioengineering and Biotechnology, 2022)
Cartilage tissue engineering technology provides a solution for treating osteoarthritis. Based on the viscoelastic nature of articular cartilage, many viscoelastic hydrogel scaffolds have been developed for investigating the effects on chondrocyte behaviors. However, cellulose nanocrystal/collagen (CNC/COL) hydrogels have not been used as a viscoelastic microenvironment to study chondrocyte growth. Here we prepared the CNC/COL hydrogels with tunable viscoelastic properties and investigated their influences on chondrocyte behaviors. The results showed that CNC and COL within the hydrogels are bonded by hydrogen bonds. The hydrogels had a microporous structure, and the viscoelastic properties were enhanced by increasing the concentration of CNC. Moreover, enhancing the hydrogel viscoelastic properties, including stress relaxation, creep, storage modulus and loss modulus, promoted the cell shape change, proliferation and matrix deposition, and reduced IL-1β level. Using principal component analysis (PCA), stress relaxation was assessed to have the strongest correlation with chondrocytes behaviors, with an authority weight value of 62.547%. More importantly, FAK and YAP were involved in the chondrocytes’ response to the rapid relaxing hydrogel by immunofluorescence staining.